Physiological and metabolic analyses provide insight into soybean seed resistance to fusarium fujikuroi causing seed decay - Chang, Xiaoli; Li, Xinyuan; Meng, Hongbai; Li, Hongju; Wu, Xiaoling; Gong, Guoshu; Chen, Huabao; Yang, Chunping; Zhang, Min; Liu, Taiguo; Chen, Wanquan; Yang, Wenyu (Frontiers in Plant Science, 2022)
Seed-borne pathogens cause diverse diseases at the growth, pre- and post-harvest stage of soybean resulting in a large reduction in yield and quality. The physiological and metabolic aspects of seeds are closely related to their defense against pathogens. Recently, Fusarium fujikuroi has been identified as the dominant seed-borne fungi of soybean seed decay, but little information on the responses of soybean seeds induced by F. fujikuroi is available. In this study, a time-course symptom development of seed decay was observed after F. fujikuroi inoculation through spore suspension soaking. The germination rate and the contents of soluble sugar and soluble protein were significantly altered over time. Both chitinase and β-1,3-glucanase as important fungal cell wall–degrading enzymes of soybean seeds were also rapidly and transiently activated upon the early infection of F. fujikuroi. Metabolic profile analysis showed that the metabolites in glycine, serine, and threonine metabolism and tryptophan metabolism were clearly induced by F. fujikuroi, but different metabolites were mostly enriched in isoflavone biosynthesis, flavone biosynthesis, and galactose pathways. Interestingly, glycitein and glycitin were dramatically upregulated while daidzein, genistein, genistin, and daidzin were largely downregulated. These results indicate a combination of physiological responses, cell wall–related defense, and the complicated metabolites of soybean seeds contributes to soybean seed resistance against F. fujikuroi, which are useful for soybean resistance breeding.